Profile of Bukit Barisan I Protection Forest, Lubuk Paraku Sub-watershed, Lubuk Kilangan District, Padang City - Mahdiyah, Naura; Leilani Eka Putri, Irma (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Forests are natural resources that play an important role in economic, social, cultural and ecological life. (Widodo & Sidik, 2020). One of the main environmental problems that arise is land damage due to deforestation and conversion of land to plantations (Akhmaddhian, 2016). Profile diagrams can be used to identify tree characteristics starting from height, crown density and width, tree architectural forms, and strata that are often used by wild animals in carrying out their daily activities (Nugraha, 2017). The purpose of this research is to learn how to make vertical and horizontal profile diagrams, to know the structure and stratification of forest vegetation in the Bukit Barisan I Protection Forest in the Lubuk Paraku sub-watershed, and to know how to cover the forest floor by the tree canopy. The research was conducted in November 2022-March 2023 in the Bukit Barisan I Protection Forest, Lubuk Paraku sub-watershed, Lubuk Kilangan District, Padang City. The method used is descriptive which begins with a field survey and then makes a single 60x20 meter plot at 2 observation stations. Then the collected data will be digitally described using the SeXI-FS application. The total number of trees in the natural forest is 37 trees of 6 different species, and in the forest adjacent to the parak 53 trees with 12 different species. The two locations are dominated by the species Villebrunea rubescens from the Urticaceae family. The structure of the vegetation at the two observation sites occupies stratum B and C, and the distribution pattern of the vegetation shows a random (uniform) distribution pattern. Thus, stratification, vegetation structure and forest floor cover structure are moderate.